The Effect of English and Pharmaceutical Integrated Learning Application on Students' Ability in Translating Pharmaceutical Texts (International Journal of Cultural and Social Science, 2022)
ntroduction Learning English and Pharmacy are two fields of study that are interrelated and complementary. Proficiency in English is very important for Pharmacy students because most of the literature and publications in the field of Pharmacy are written in English. However, most Pharmacy students experience difficulties in understanding the literature and publications due to their limited English skills. Therefore, learning strategies are needed that can improve English language skills and translation skills of Pharmacy students. One of the learning strategies that can be implemented is integrated learning between English and Pharmacy. This integrated learning can help students understand Pharmacy texts written in English more easily and effectively. However, very little research has been conducted to determine the effect of implementing this integrated learning on the ability to translate Pharmacy students. Objective The aim of this study was to determine the effect of implementing integrated learning in English and Pharmacy on students' ability to translate pharmaceutical texts. Method The research method used was a pretest-posttest control group design with a sample of 60 students of the X University Pharmacy Study Program. The sample was divided into two groups, namely the experimental group and the control group. The experimental group was given integrated learning in English and pharmacy, while the control group was given conventional learning.. Results The results showed that there was a significant difference between the ability to translate pharmacy texts before and after the implementation of English and pharmacy integrated learning in the experimental group. Whereas in the control group, there was no significant difference between the ability to translate pharmaceutical texts before and after conventional learning. The interviews showed that the obstacles faced by students in translating pharmaceutical texts were limited knowledge of English and limited knowledge of pharmacy. Integrated learning of English and pharmacy helps overcome these obstacles by providing more focused and structured teaching on both aspects. Conclusion It can be concluded that the application of English and pharmacy integrated learning can improve students' ability to translate pharmaceutical texts. Therefore, integrated learning of English and pharmacy can be used as an alternative learning strategy that is more effective and efficient in improving the quality of pharmacy education in Indonesia.